Drug Screening Implicates Chondroitin Sulfate as a Potential Longevity Pill - Ewald, Collin Y. (Frontiers in Aging, 2021)
Discovering compounds that promote health during aging (‘geroprotectors’) is key to the retardation of age-related pathologies and prevention of chronic age-related diseases. In in-silico and model organisms' lifespan screens, chondroitin sulfate has emerged as a geroprotective compound. Chondroitin sulfate is a glycosaminoglycan attached to extracellular matrix proteins and is naturally produced by our body. We have recently shown that chondroitin sulfate supplementation increases the lifespan of C. elegans. This review discusses the two major potential mechanisms, extracellular matrix homeostasis and inhibition of inflammation, that counteract age-related pathologies upon chondroitin supplementation. Oral supplementation with chondroitin sulfate is well tolerated, and after absorbance, gets to the target tissue. Chondroitin sulfate supplementation is associated with human longevity in large cohort studies and showed efficacy in slowing age-related diseases in randomized clinical trials. Thus, chondroitin sulfate holds the potential to become a geroprotective strategy to promote health during human aging.